The antioxidant/anticancer potential of phenolic compounds isolated from olive oil - Owen, Robert; Hull, William Edmund; Spiegelhalder, Bertold; Bartsch, Helmut (European journal of cancer, 2000)
In our ongoing studies on the chemoprevention of cancer we have a particular interest in the health benefits of the Mediterranean diet, of which olive oil is a major component. Recent studies have shown that extravirgin olive oil contains an abundance of phenolic antioxidants including simple phenols (hydroxytyrosol, tyrosol), aldehydic secoiridoids, flavonoids and lignans (acetoxypinoresinol, pinoresinol). All of these phenolic substances are potent inhibitors of reactive oxygen species attack on, e.g. salicylic acid, 2-deoxyguanosine. Currently there is growing evidence that reactive oxygen species are involved in the aetiology of fat-related neoplasms such as cancer of the breast and colorectum. A plausible mechanism is a high intake of ω-6 polyunsaturated fatty acids which are especially prone to lipid peroxidation initiated and propagated by reactive oxygen species, leading to the formation (via α,β-unsaturated aldehydes such as trans-4-hydroxy-2-nonenal) of highly pro-mutagenic exocyclic DNA adducts. Previous studies have shown that the colonic mucosa of cancer patients and those suffering from predisposing inflammatory conditions such as ulcerative colitis and Crohn's disease generates appreciably higher quantities of reactive oxygen species compared with normal tissue. We have extended these studies by developing accurate high performance liquid chromatography (HPLC) methods for the quantitation of reactive oxygen species generated by the faecal matrix. The data shows that the faecal matrix supports the generation of reactive oxygen species in abundance. As yet, there is a dearth of evidence linking this capacity to actual components of the diet which may influence the colorectal milieu. However, using the newly developed methodology we can demonstrate that the antioxidant phenolic compounds present in olive oil are potent inhibitors of free radical generation by the faecal matrix. This indicates that the study of the inter-relation between reactive oxygen species and dietary antioxidants is an area of great promise for elucidating mechanisms of colorectal carcinogenesis and possible future chemopreventive strategies.